MANAJEMEN HARMONI: MENGGALI AKAR FILSAFAT CONFUCIUS UNTUK PRAKTIK MANAJERIAL YANG EFEKTIF - lianto, lianto (MABIS, 2012)
According to Max Weber, Confucianism will be an inhibiting force in Asian economic development. Confrontated with China amazing economic growth, it appears that Weber might have not been correct. Chinas recent and impressive economic growth has captured the world attention. As the worlds fastest growing economic country, china is poised toÂ change the landscape of global business. The increased importance of China in the world economy has heightened the necessity of understanding Chinese management practices. This paper attempts to provide an understanding of Chinese culture and management practices by exploring the historical roots of Chinese cultural values.